The Dynamics Of The Current Account Behavior In The ASEAN-5 Countries - Lau, Evan Poh Hock (2004)
The current account is an endogenous variable that contains information about the behaviors of the economics agents. Thus, it is important for economic policymaking as it gives a broad reflection of the stance of macroeconomics policies. This dissertation empirically analyzed the anatomy of the dynamic current account behavior for the ASEAN-5 countries using three closely related elements. These includes evaluating the dynamic current account behavior using the present value model, the sustainability of current account imbalances and the interconnection between twin deficits phenomenon in the ASEAN-5 economies. Several important results are summarized from this study. First, the statistical estimation from the present value model suggests that the agents behave as the forward-looking rational agents in the face of the shocks in the three out of five economies. This implies that the current account acts as a buffer to smooth the consumption in the presence of shock and optimally smoothing its consumption path for these countries. Second, the sustainability analysis clearly indicates that for all countries, (except Malaysia and Singapore), current account deficits were not on the long-run steady state in the pre-crisis (1961-1997) era. An important lesson from this result is that the large and persistent external imbalances can trigger a financial crisis. The policy action to correct the widening of current account deficits should have taken place prior to 1997 when the external imbalances were on the unsustainable path. In other words, the external imbalances may be used as an indicator (or early warning signal) for a forthcoming crisis. Third, we found two channel of causal relationship between budget and current account deficits which (i) directly transmitted between budget and current account deficit and (ii) budget deficit is the driving force for interest rate, exchange rate and current account. Solving and managing the current account problem had been the center of international economic policymaking in many countries around the globe. As such, the issues presented in this study would serve as important guidelines for the understanding of the co-movements of the current account behavior and provide a platform for debate on the experiences of developing countries in promoting macroeconomic stability and sustainability in their countries.